Beta-lactamase resistance genes in Enterobacteriaceae from Nigeria - Babafela B. Awosile; Michael Agbaje; Oluwawemimo Adebowale; Olugbenga Kehinde; Ezekiel Omoshaba (African Journal of Laboratory Medicine, 2022)
Background: Beta-lactamase genes are one of the most important groups of antimicrobial resistance genes in human and animal health. Therefore, continuous surveillance of this group of resistance genes is needed for a better understanding of the local epidemiology within a country and global dissemination.